Floquet's Unit Cell Design for Periodic Structures at Optical Frequencies. (23rd September 2009) - Massaro, Alessandro; Cingolani, Roberto; Passaseo, Adriana; De Vittorio, Massimo
Abstract : We present a new theoretical approach regarding the design of 2D periodic structure at optical frequencies. The model is based on Floquet's theory and on the variational equivalent circuit. The distributed circuit model is developed through the use of the microwave network theory and the optical theory of the step discontinuities. This approach analyzes 2D dielectric periodic structures with high dielectric contrast by the transmission line model including variational equivalent circuits. The 3D Finite Element Method (FEM) model validates Floquet's design theory of the grating resonance and provides the design optimization of an optical GaAs periodic waveguide.